2001
DOI: 10.1159/000054679
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5-HT<sub>1A</sub> Receptor mRNA Expression in Dorsal Hippocampus and Raphe Nuclei after Gonadal Hormone Manipulation in Female Rats

Abstract: Female ovarian steroids influence mood and cognition, an effect presumably mediated by the serotonergic system. A key receptor in this interplay may be the 5-HT1A receptor subtype. We gave adult ovariectomized female rats subcutaneous pellets containing different dosages of 17β-estradiol alone or in combination with progesterone, or placebo pellets, for 2 weeks. 5-HT1A receptor mRNA levels were analyzed by in situ hybridization in the dorsal hippocampus, dorsal and median raphe nuclei, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 44 publications
3
34
0
1
Order By: Relevance
“…In addition, estrogen induces progesterone receptor expression in the dorsal raphe nucleus (Bethea, 1994). Previous studies have suggested that estrogen reduces 5-HT 1A receptor gene expression and the addition of progesterone enhances this effect on 5-HT 1A autoreceptors (Pecins- Thompson and Bethea, 1999) but reverses the effect of estrogen on the postsynaptic 5-HT 1A receptors (Birzniece et al, 2001). Therefore, one explanation for the present results could be that estrogen induces progesterone receptor expression in the dorsal raphe nucleus, and together these hormones significantly inhibit 5-HT 1A autoreceptor expression, reducing the effect of 8-OH-DPAT on PPI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, estrogen induces progesterone receptor expression in the dorsal raphe nucleus (Bethea, 1994). Previous studies have suggested that estrogen reduces 5-HT 1A receptor gene expression and the addition of progesterone enhances this effect on 5-HT 1A autoreceptors (Pecins- Thompson and Bethea, 1999) but reverses the effect of estrogen on the postsynaptic 5-HT 1A receptors (Birzniece et al, 2001). Therefore, one explanation for the present results could be that estrogen induces progesterone receptor expression in the dorsal raphe nucleus, and together these hormones significantly inhibit 5-HT 1A autoreceptor expression, reducing the effect of 8-OH-DPAT on PPI.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has been found to reduce 5-HT 1A receptor gene expression in the dorsal raphe nucleus (Pecins- Thompson and Bethea, 1999), regions of the hippocampus (Birzniece et al, 2001) and amygdala (Ö sterlund and Hurd, 1998). Progesterone further reduces 5-HT 1A receptor gene expression in the dorsal raphe nucleus of estrogen-primed animals (Pecins- Thompson and Bethea, 1999); however, it increases 5-HT 1A receptor gene expression in the hippocampus (Birzniece et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rats underwent ovariectomy (OVX) followed by continuous release pellet implantation (.5 mg of 17β estradiol [E2] and 50 mg of progesterone [P4] 21-day release or placebo) (Innovative Research of America, Sarasota, Florida) under pentobarbital/ atropine anesthesia to mimic serum levels of those during human pregnancy (11). After 21 days treatment, the hormone pellets were completely removed under isoflurane anesthesia.…”
Section: Hormone-simulated Pseudopregnancy-human and Hormone-simulatementioning
confidence: 99%
“…However, this regimen was based on the plasma concentration of estrogen and progesterone that occurs in the course of rat pregnancy, where progesterone peaks during the middle of gestation and falls to estrous cycle levels by the time of delivery (10). Conversely in humans, both estrogen and progesterone increase gradually throughout the pregnancy (11). Progesterone has been shown to alter neurotransmission, indicating a crucial role in the pathophysiology of PPD (3).…”
mentioning
confidence: 99%